Rising Damp Treatment in Historical Buildings by Electro-Osmosis: A Case Study - Koca, Aliihsan; UĞURAL, MEHMET NURETTİN; YAMAN, ERGÜN (MDPI, 2024)
Throughout the past century, numerous technologies have been suggested to deal with the capillary rise of water through the soil in historic masonry buildings. The aim of this study was to examine the effectiveness of capillary moisture repulsion apparatus that uses the electro-osmosis approach over a prolonged period of time. The G & uuml;l mosque was selected as a sample historical building affected by structural problems caused by the absorption of water through small channels on its walls due to capillary action. The moisture repulsion mechanism efficiently decreased the moisture level in the walls from a 'wet' state to a 'dry' state in roughly 9 months. After the installation of the equipment, the water mass ratio of the building decreased from 14.48% to 2.90%. It was determined that the majority of the water in the building was relocated during the initial measurement period. Furthermore, it inhibited the absorption of water by capillary action by protecting the construction elements that were in contact with the wet ground. Lastly, capillary water repulsion coefficients (C) for various measurement durations and time factors were proposed. The average value of C was calculated to be 0.152 kg/m2 s0.5 by measuring the point at which the water repulsion remained nearly constant.
Keywords: Capillarity; Construction; Electro-osmosis; Humidity; Masonry; Project Management; Rising Damp